METAMOFORSIS DAN PROSPEK PARTAI POLITIK ISLAM INDONESIA - Adib Fathoni (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2013)
Islamic politics substantially is a response of Islam to power and state, which produce political behaviour, culture and attitude based on Islamic values.The Dilema of Islamic Politics roots from some basic problems that exist in moslem political life. Some problems are teological, like relations between religion and state. The culture dimension in some moslem groups make it hard to be unified in political life.In this context, unification of Islamic Parties is almost an utopia. Pluralism in Islamic society. Further, pluralism in Islamic society is logical consequence from Islamization process in archipelago state, which have different intencity between one place and the others.